Pemberdayaan UMKM Wedang Rempah 3 Putri melalui Pemanfaatan Platform Prospek Digital untuk Peningkatan Daya Saing Global - Hastuti, Indra; Sopingi Sopingi; Singgih Purnomo; Annisa Ita Yulianti; Arfandi Prasetyo (Pusat Riset dan Inovasi Nasional, 2025)
This Community Service Program (PKM) was implemented at UMKM Wedang Rempah 3 Putri Sukoharjo with the aim of enhancing competitiveness through the application of e-prospek, strengthening digital marketing, and product diversification into ready-to-drink (RTD) beverages. The program employed mentoring, training, and hands-on practice, engaging UMKM actors actively from the planning stage to implementation. The results show that the use of the e-prospek application successfully expanded market access, digital marketing improved promotional effectiveness, and RTD product diversification attracted modern consumers who value practicality and health benefits. Beyond the economic impact of increased sales, the program fostered digital awareness, local leadership, and community independence. Theoretically, these findings reinforce the literature on the significance of digital transformation and product innovation in community-based MSME empowerment. This program is recommended for sustainable development through enhanced digital literacy, stronger local branding, and multi-stakeholder collaboration to establish an adaptive, innovative, and competitive MSME empowerment model.